Influence of traditionally used Nepalese plants on wound healing and immunological properties using primary human cells in vitro. (10th May 2019) - Zimmermann-Klemd, Amy M.; Konradi, Viktoria; Steinborn, Carmen; Ücker, Annekathrin; Falanga, Chiara Madlen; Woelfle, Ute; Huber, Roman; Jürgenliemk, Guido; Rajbhandari, Meena; Gründemann, Carsten
Abstract: Ethnopharmacological relevance: The improvement of wound healing has always been an important issue for both ethnopharmacological and modern medical research. In this study, we used state-of-the-art methods to investigate extracts of plants used traditionally in Nepal for more than 1000 years to treat inflammatory injuries. Aim of the study: We focused on the potential of the plant extracts to ameliorate wound healing and to influence immune modulatory properties. Materials and methods: Nine Nepalese plant extracts in three different solvents (methanol, ethyl acetate, petroleum ether) were immunologically characterised. Water-soluble tetrazolium (WST-1) assays and scratch assays were performed to determine their impact on viability and wound healing capacity of human keratinocytes and fibroblasts. Effects on proliferation, viability and function of physiologically relevant anti-CD3 and anti-CD28 stimulated primary human T lymphocytes were assessed using carboxyfluorescein succinimidyl ester (CFSE), annexin V/propidium iodide staining assays and flow cytometry–based surface receptor characterisation. The secretion level of interleukin-2 (IL-2) was analysed with the ELISA technique. Dendritic cells were generated out of peripheral blood mononuclear cells (PBMC) by CD14 + magnetic bead selection. Flow cytometry-based surface receptor characterisation and ELISA-based technique were used to evaluate the DC activation state and the interleukin-8 (IL-8) secretion level. Results: We demonstrate that an ethyl acetate extract of Bassia longifolia and of Gmelina arborea have anti-inflammatory capacities, indicated by reduced proliferation, inhibition of IL-2 secretion and degranulation capacity of activated human T cells, when compared with adequate concentrations of synthetic positive drug controls. Furthermore, Gmelina arborea improved the wound healing of keratinocytes and fibroblasts and has tendency to increase the secretion of IL-8 by human primary dendritic cells. Conclusion: With this preliminary screening, we offer a scientific basis for the immunomodulatory properties of the two Nepalese medicinal plants Bassia longifolia and Gmelina arborea . However, further detailed studies regarding the responsible compounds are necessary. Graphical abstract: fx1